Pembuatan Alat Penghancur Sampah Infeksius Jenis Popok dan Pembalut Sekali Pakai untuk Optimalisasi Pengelolaan Sampah TPS3R Desa Tanjungrejo - Afriliana, Ryo; Wijaya, Chandra Adi; Imawati, Iftitah; Iresha, Fajri Mulya; Mubarok, Husein; Wahyuni, Elvira (Journal of Appropriate Technology for Community Services, 2025)
One of the urgent issues worldwide is infectious waste, which impacts both the environment and health. Infectious waste includes various types of medical waste, such as disposable diapers and sanitary pads contaminated with hazardous materials like blood, bodily fluids, and other pathogens. If not properly managed, infectious waste can lead to the spread of diseases. The village of Tanjungrejo, located in the Ngombol subdistrict, has a well-managed TPS3R Waste Bank, but one of the issues they face is the lack of a management method for infectious waste like disposable diapers and sanitary pads. In Tanjungrejo, infectious waste is often disposed of by being dumped into streams or burned along with other waste due to the lack of proper facilities for managing infectious waste. This method of waste management can lead to the transmission of diseases and environmental pollution, such as water, air, and soil contamination. Based on these issues, the aim of this community service project is to develop technologies and innovations to help address environmental problems, including the management of infectious waste. The project will use the Design Thinking method, which includes the stages of empathize, define, ideate, prototype, and test.